Implementasi Sistem Informasi Geografis (SIG) Untuk Pemetaan Lokasi Rawan Banjir Di Kabupaten Kebumen - Alfi Karomah; Hamzah Muhammad Mardi Putra (DPPM Universitas Pelita Bangsa, 2022)
Flooding is a condition in which water cannot be accommodated in the drain channel (river channel) or the flow of water in the drain channel is blocked, so that it overflows and inundates the surrounding area (flood plain). Mapping of flood distribution areas using remote sensing satellites and GIS can be done by combining flood phenomena and satellite capabilities. The purpose of this study is to identify the use of geographic information systems for mapping flood-prone areas in Kebumen district and identify flood-prone areas in Kebumen district. The research method is in the form of descriptive quantitative surveys and descriptions to determine the mapping of flood-prone areas in Kebumen district using overlay and scoring functions using ArcGIS 10.3 software. The results showed that spatial and non-spatial data processing was divided into three classes of flood-prone areas. The flood-prone area is 182 ha, the flood-prone area is 276 ha, and the non-prone area is 1.09 ha. Keywords: GIS, Floods, Mapping